Re-thinking the Role of Rural Tourism. Potentials for a Sustainable Transborder Tourism in the Area Bulgaria-Greece - Krasteva, Rouska; Kiryakova-Dineva, Teodora (European Journal of Sustainable Development, 2018)
The paper aims to analyze the transborder area between South-West Bulgaria and Northern Greece through the lenses of sustainable rural tourism. The research evaluates the potentials for rural tourism by exploring the competitiveness of the chosen borderland. The applied qualitative analysis uses the complex aggregate indicator of competitiveness which is comprised of twelve criteria. The final aim of research is to emphasize the role of rural tourism so to rethink the possibilities of a common transborder strategy for sustainable rural tourism. The interesting and unique aspect of the study lays in its holistic approach and its deductive character. Keywords: rural tourism, transborder area Bulgaria-Greece, competitiveness analysis and evaluation, sustainability